Nanocrystallography measurements of early stage synthetic malaria pigment. Issue 5 (29th September 2017) - Dilanian, Ruben A.; Streltsov, Victor; Coughlan, Hannah D.; Quiney, Harry M.; Martin, Andrew V.; Klonis, Nectarios; Dogovski, Con; Boutet, Sébastien; Messerschmidt, Marc; Williams, Garth J.; Williams, Sophie; Phillips, Nicholas W.; et al.
Abstract : Serial femtosecond crystallography (SFX) at an X‐ray free‐electron laser enables crystllographic data to be collected from samples orders of magnitude smaller than at a synchrotron. Here SFX is used to investigate the nascent structure of β‐hematin derived from nanocrystals and this is compared with the well known structure derived from macroscopic crystals of the same material. Abstract : The recent availability of extremely intense, femtosecond X‐ray free‐electron laser (XFEL) sources has spurred the development of serial femtosecond nanocrystallography (SFX). Here, SFX is used to analyze nanoscale crystals of β‐hematin, the synthetic form of hemozoin which is a waste by‐product of the malaria parasite. This analysis reveals significant differences in β‐hematin data collected during SFX and synchrotron crystallography experiments. To interpret these differences two possibilities are considered: structural differences between the nanocrystal and larger crystalline forms of β‐hematin, and radiation damage. Simulation studies show that structural inhomogeneity appears at present to provide a better fit to the experimental data. If confirmed, these observations will have implications for designing compounds that inhibit hemozoin formation and suggest that, for some systems at least, additional information may be gained by comparing structures obtained from nanocrystals and macroscopic crystals of the same molecule.